Can the season of burning affect the growth of Dichrostachys cinerea populations: A hypothesis of phenology - Schutz, Alex (Department of Biological Sciences, 2024)
A hypothesis was put forward that summer burning would constrain the population growth of Dichrostachys cinerea as at this stage in the plant's phenology carbon reserves are lowest after the initial spring flush and therefore post-bum re-growth would be stunted. Initial slow re-growth would affect the time taken to reach maturity and the size of the plant in the next bum, thus indirectly affecting both fertility and mortality. The hypothesis was tested by collecting data pertaining to the different fertility, growth and persistence levels of D. cinerea populations in long term experimental bum plots that have been burnt in different months and at different frequencies. The change in population density of D. cinerea in the plots over the last half-century was also investigated to test whether any short term effects of the season of fire on a particular generation have long-term repercussions on the population density of the species. The particular life-history of D. cinerea was also investigated and compared against that of Acacia nigrescens. It was the average size of plants and their fertility levels are generally lower for plants burnt in mid-summer compared to plants burnt in winter. On all the bum plots investigated D. cinerea population numbers have increased n the last half century but averaged across the study areas these increases are most pronounced on winter triennial bums.